Interfacial atomic Ni tetragon intercalation in a NiO2-to-Pd hetero-structure triggers superior HER activity to the Pt catalyst. Issue 20 (25th March 2021) - Li, Haolin; Dai, Sheng; Bhalothia, Dinesh; Hu, Alice; Chou, Jyh-Pin; Chen, Tsan-Yao
Abstract : Electron relocation pumps charge from Ni via tensile strain of doped Ni tetragons, compression strain of surrounding Pd atoms and the inherent electronegative difference, thus promising prominent hydrogen evolution efficiency for the Pd surface. Abstract : The design of highly efficient, low-cost and long-term stable electrocatalysts for the hydrogen evolution reaction (HER) is a research hotspot in the field of sustainable energies ( e.g., fuel cells). In this study, a novel catalyst design comprising NiO2 supported Pd nanocatalysts (NCs) with an interfacial atomic cluster of Ni metal is proposed and their HER activity with the corresponding reaction mechanism is systematically investigated by using density functional theory (DFT) calculations. For the optimum case with four Ni atoms in a tetragonal shape ( i.e., NiO2 –Ni4 –Pd), the reaction coordinate (barrier) is reduced by 0.36 eV and 0.34 eV respectively in the Volmer and Tafel steps among models with different amounts of Ni atoms. The corresponding results reveal that the novel steric confinement effects of the atomic Ni-ensemble tetragon will unbalance the surface charge distribution to generate the local domain heterogeneity on the Pd-shell surface and further prove the doping threshold of the Ni tetragon in terms of HER-kinetics improvement. For evaluating the rationales on experimental variations by the inevitable interatomic intermix in a rapid crystal growth process, the results of various atomic doping ratios of Ni d /Pd from ∼2% to 67% are systematically investigated. The adsorption energy of H* is even lower than that on Pt by further increasing Ni atoms to 32, therefore, showing the potential capability of such a type of structure design for catalysts in the HER. Based on the presented results, we believe that our research can be applied to guide the adjustment of heterogeneous catalysts in the experimental synthesis while offering a theoretical insight for designing transition metal oxide-based systems toward inexpensive, efficient and green initiative merits.